Breast Cancer 2022
DOI: 10.36255/exon-publications-breast-cancer-usp18
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Specific Peptidase 18: A Multifaceted Protein Participating in Breast Cancer

Abstract: published in pdf, html, and xml formats as shown under Catalogue upon editorial acceptance of all chapters. The citation details will not change even after the publication of the book in its final format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Specifically in tumorigenesis, the roles of free ISG15 and ISGylation are not well‐defined, despite many studies. Some studies suggest that protein ISGylation is an antagonistic system to the ubiquitination system in order to provide stability to proteins in breast cancer cells (Pinto‐Fernandez et al., 2021 ; Tecalco‐Cruz et al., 2022 ). Concurrent to the above findings, we have shown that ISGylation of STAT3 in ascites cells may be contributing to its stability and increasing the sEV release.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in tumorigenesis, the roles of free ISG15 and ISGylation are not well‐defined, despite many studies. Some studies suggest that protein ISGylation is an antagonistic system to the ubiquitination system in order to provide stability to proteins in breast cancer cells (Pinto‐Fernandez et al., 2021 ; Tecalco‐Cruz et al., 2022 ). Concurrent to the above findings, we have shown that ISGylation of STAT3 in ascites cells may be contributing to its stability and increasing the sEV release.…”
Section: Discussionmentioning
confidence: 99%